Turkish Historiography on the Forced Migration of the Turks of Bulgaria to Turkey of 1989 - Solakoglu, Memed Sarp; Herguvenc, Begum (SOUTH-WEST UNIV NEOFIT RILSKI, 2021)
The history of the Turks of Bulgaria, following the forced migration that took place in 1989, became a topic highly studied in the Turkish academia. Although many scholars who are focused on the topic are in consensus about what happened between 1984 and 1989, it is less so the case in the period prior to it. In this study of reviewing the Turkish literature (or literature in Turkish) on the Forced Migration of 1989, it is aimed to provide the opinions and comments written by the Turkish scholars on the relations between the Turks and the Bulgarians of Bulgaria regarding the Forced Migration of 1989 and to show that there are discrepancies in the periodizations of the history of Bulgaria even though the main narratives overlap each other almost unanimously. To do so, this study features the interpretations of the agricultural and educational policies in Bulgaria and the dates of changes in these policies according to the scholars and researchers will be provided. The basis of their interpretations will also be included. Finally the perception of the identity of the Turks of Bulgaria prior to 1984 and its relations to that of Turks of Turkey after 1989 will be examined.
Keywords: Forced Migration of 1989; Turks of Bulgaria; literature review; identity; Arts & Humanities - Other Topics